Iridoid Compounds and Antimicrobial Activity of the Roots of Tecoma stans(L) Juss - Ganapaty, S.; Nyamathulla, S.; Srilakshmi, G.V.K.; Raj Kumar, P.V. (Asian Journal of Chemistry, 2010)
The combined ethyl acetate and methanolic extracts of the roots of Tecoma stans gave two iridoid compounds, 5-deoxystantioside, plantarenaloside when subjected to chromatographic techniques. In addition to iridoid compounds luteolin, lupeol acetate and β-sitosterol were also isolated. The structures of these compounds were determined by spectral means (1H NMR, IR, UV, MS). Further the extracts and the isolates were subjected to antimicrobial studies, which showed moderate activity.